Rasisme Dalam Film 99 Cahaya di Langit Eropa Part 1(Analisis Semiotika Dalam Film 99 Cahaya Di Langit Eropa Part 1) - Rita, Vallen Nur; , Rinasari Kusuma, M. I. Kom; , Yanti Haryanti, M. A. (2016)
Vallen Nur Rita. L100100007, Racism in Film 99 Cahaya di Langit Eropa Part 1 (Analysis of Semiotics In Film 99 Cahaya di Langit Eropa Part 1),Thesis, Communication Studies, Faculty of Communication and Informatics, University of Muhammadiyah Surakarta, 2016 . Stereotyping is a negative statement of prejudice. Prejudice is then used as an excuse to discriminate against certain racial groups. Stereotypes and prejudices then refer to a notion that the belief in the superiority which denied the equality of man, namely racism. The behavior and acts of racism have appeared in some films scenes 99 Cahaya di Langit Eropa Part 1. The purpose of this study was to determine how symbols are used to describe racism in film 99 Cahaya di Langit Eropa Part 1. The methods used by researchers is semiotic Roland Barthes. Model Roland Barthes consists of three stages of analysis of denotation, connotation, myth. Researchers conducted an analysis using verbal and nonverbal signs contained in the film "99 Cahaya di Langit Eropa Part 1". In analyzing the films 99 Cahaya di Langit Eropa Part 1, grouped into several categories related to the behavior of racism, among others: the stereotypes, prejudice, discrimination. Stereotypes are shown in the movie 99 Cahaya di Eropa Part 1 form setereotip against the Muslim Turks as occupiers were defeated and stereotypes against hijab wearer is considered the same as the occupiers (Kara Mustafa). Prejudice in this film include religion is considered difficult because the rules of clean and unclean foods, God is considered only on Fridays, and prejudice against Muslim women who pray in the Mezquita cathedral. Discrimination include banning prayer for Muslim students on campus and the banning of wearing headscarves in schools and the work environment area. All acts of racism that occurred in this film led to the scene of the attack the city of Vienna by the Turkish Muslim forces led by Kara Mustafa. Austrian Society could not easily forget the attack, and make defeat Turkey as a tool to impose Muslim Turkey at the present time to the action Racism.